Mantenimiento de Casona - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observo un mantenimiento de una de las casonas de iqutos, tambien podemos ver a personal militar del Ejercito del Peru.
ENGLISH: On December 15, 1981 and by Law No. 23339, the name was changed to Gerencia Micro Regional de Alto Amazonas, within the structure of the Departmental Corporation of Loreto (CORDELOR).

SPANISH: Se observo un mantenimiento de una de las casonas de iqutos, tambien podemos ver a personal militar del Ejercito del Peru.
ENGLISH: On December 15, 1981 and by Law No. 23339, the name was changed to Gerencia Micro Regional de Alto Amazonas, within the structure of the Departmental Corporation of Loreto (CORDELOR).
Maintenance of Casona
Keywords: Iquitos (Perú)|~|Maintenance|~|Inspection and refurbishment|~|Historic houses|~|Iquitos (Perú)|~|Mantenimiento|~|Perú|~|Inspección y Refacción de Casas Historicas|~|Mantenimiento|~|Iquitos (Peru)|~|Maintenance|~|Inspection and Refurbishment of Historic Houses|~|Maintaining